Conditions and Models for Implementing Multi-Actor Participation in Rural Homestead System Reform: A Case Study of Jiangxi Province - Wang, Huiji; He, Shasha; Liu, Zheng (International Journal of Social Sciences and Public Administration, 2024)
The reform of rural homestead land is a critical component of global efforts to enhance rural governance, optimize land use, and improve the livelihoods of rural residents. This study explores the implementation conditions and models for multi-actor participation in homestead system reform, focusing on the role of government, villagers, and social organizations. Using Jiangxi Province in China as a case study, we highlight collaborative governance mechanisms that facilitate successful reform, including institutional frameworks, community engagement, and the role of intermediaries. The findings indicate that a well-structured collaboration between stakeholders can effectively address issues of land allocation, resource utilization, and sustainable rural development. Policy recommendations are provided to enhance the inclusiveness and effectiveness of the reform process, emphasizing the importance of participatory governance, transparent decision-making, and capacity building at the community level. The lessons learned can contribute to similar rural land reforms in other regions globally, promoting sustainable and equitable development.